Pengaruh Penggunaan Model Problem Based Learning Terhadap Kemampuan Koneksi Matematis Siswa di Kelas IV SDN 01 Bandar Buat - Oktavia, Rianti; Dalais, Mursal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The background of the research was the low of data about the mathematical connection skill for elementary students. The aim of te research is inding out the effect of problem based learning to the mathematical connection skill at the fourth level IV of SDN 01 Bandar Buat. The kind of he research was quantitative in the design esperriment quasy form. The population of the research was the students of the fourth level IV of SDN Komplek Blok D Unand the included from 2(two) schools. It was with sampling random simple technique, it go the SDN 011 Bandar Buat, which was the SDB 01 Bandar Buat had 2(two) class. The instrument of the research was the written test in essay from. The technique of data analysis was t-test. Based on the result of research, it found the average score of post-test about the mathematical connection skill by Problem Based Learning model in experiment group was 83,8 and control group that used conventional learning was 65,36. So, the result was the average of experiment group was highest than control group. Based on the calculation of t-test, it got t-obtain 6,893 while t-table 0,05 and dk=58 was 2,00. The mean was t-obtain > t-table and Problem Based Learning model to the student’s mathematical connection skill at IV SDN 011 Bandar Buat.            Keywords: Problem Based Learning model, mathematical connection.